Chronic Myeloid Leukemia and Hepatoblastoma: Two Cancer Models to Link Metabolism to Stem Cells - Cipolleschi, Maria Grazia; Marzi, Ilaria; Rovida, Elisabetta; Dello Sbarba, Persio (Frontiers in Oncology, 2016)
Low oxygen tension is a critical aspect of the stem cell niche where stem cells are long-term maintained. In “physiologically hypoxic” stem cell niches, low oxygen tension restrains the clonal expansion of stem cells without blocking their cycling, thereby contributing substantially to favor their self-renewal. The capacity of stem cells, hematopoietic stem cells in particular, to reside in low oxygen is likely due to their specific metabolic profile. A strong drive to the characterization of this profile emerges from the notion that cancer stem cells (CSC), like normal stem cells, most likely rely on metabolic cues for the balance between self-renewal/maintenance and clonal expansion/differentiation. Accordingly, CSC homing to low oxygen stem cell niches is the best candidate mechanism to sustain the so-called minimal residual disease. Thus, the metabolic profile of CSC impacts long-term cancer response to therapy. On that basis, strategies to target CSC are intensely sought as a means to eradicate neoplastic diseases. Our “metabolic” approach to this challenge was based on two different experimental models: (A) the Yoshida’s ascites hepatoma AH130 cells, a highly homogeneous cancer cell population expressing stem cell features, used to identify, in CSC adapted to oxygen and/or nutrient shortage, metabolic features of potential therapeutic interest; (B) chronic myeloid leukemia, used to evaluate the impact of oxygen and/or nutrient shortage on the expression of an oncogenetic protein, the loss of which determines the refractoriness of CSC to oncogene-targeting therapies.